Treatment agent for metal materials and metal material having coating film
A post-treatment agent with specific polymers and molybdate/tungstate ions forms a protective film on metal surfaces, addressing the inadequacy of existing agents to enhance corrosion resistance in coated metals.
Patent Information
- Application Number
- JP2024172393
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-01
- Publication Date
- 2024-12-13
AI Technical Summary
Existing chemical conversion treatment agents for metal materials do not adequately enhance the corrosion resistance of coated metal surfaces.
A post-treatment agent containing polymers with specific structures and molybdate or tungstate ions is applied after chemical conversion treatment to form a chemical conversion film, improving corrosion resistance.
The treatment agent significantly enhances the corrosion resistance of coated metal materials by forming a protective film that withstands environmental degradation.
Smart Images

Figure 2024174137000001 
Figure 2024174137000002 
Figure 2024174137000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a treatment agent used in post-treatment of a chemical conversion treatment for forming a chemical conversion coating on the surface or surface of a metal material, and to a metal material having a coating film. [Background technology]
[0002] Conventionally, various chemical conversion coating agents and surface treatment agents have been developed to improve the corrosion resistance of coated metal materials. For example, Patent Document 1 discloses a pretreatment agent for metal materials used in pretreatment for chemical conversion coating, which is a blend of a specific polymer and water. Furthermore, Patent Document 2 discloses a method for anti-corrosion pretreatment of a metal surface including steel, galvanized steel, aluminum, magnesium, and / or a zinc-magnesium alloy, which comprises contacting the metal surface with an aqueous composition A containing a specific amount of a copolymer containing specific monomer units, and an acidic aqueous composition B containing at least one compound selected from the group consisting of titanium, zirconium, and hafnium compounds. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 087320 [Patent Document 2] Special Publication No. 2019-518874 Summary of the Invention [Problem to be solved by the invention]
[0004] Although the above pretreatment agents have been proposed to improve the corrosion resistance of coated metal materials, there is a need to develop other means. An object of the present invention is to provide a new means for improving the corrosion resistance of coated metal materials. [Means for solving the problem]
[0005] As a result of intensive research conducted by the inventors in order to solve the above problems, they discovered that by carrying out post-treatment of a chemical conversion treatment using a treatment agent containing a polymer having a specific structure, a metal material having a coating film formed after the post-chemical conversion treatment has excellent corrosion resistance, which led to the completion of the present invention.
[0006] The means for solving the above problems are as follows. [1] A treatment agent used for a surface of a metal material or for a post-treatment of a chemical conversion treatment for forming a chemical conversion coating on the surface, the treatment agent comprising: (A) one or more compounds or polymers selected from a compound or polymer having -NH2, a compound or polymer having -NH2 and -NH-, and a compound or polymer having -NH-, which are water-soluble or water-dispersible; A treatment agent comprising: [2] The treatment according to [1], further comprising at least one metal acid ion (B) selected from a molybdate ion and / or a tungstate ion. [3] A metal material having a coating film, which is obtained by contacting the treatment agent according to [1] or [2] with a chemical conversion coating of a metal material having the chemical conversion coating, and then painting the metal material. Effect of the Invention
[0007] According to the present invention, it is possible to provide a treatment agent capable of improving corrosion resistance when a coating film is formed on a chemical conversion film, and a metal material having a coating film obtained by contacting the treatment agent with a chemical conversion film on a metal material having the chemical conversion film and then painting the metal material. . DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The treatment agent according to the embodiment of the present invention is a treatment agent used in post-treatment carried out after chemical conversion treatment for forming a chemical conversion coating on the surface or surface of a metal material. The treatment agent is also a pre-painting treatment agent. In other words, the treatment agent is used after chemical conversion treatment and before painting. The treatment agent is a treatment agent containing one or more compounds or polymers (A) selected from water-soluble or water-dispersible compounds or polymers having -NH2, compounds or polymers having -NH2 and -NH-, and compounds or polymers having -NH-. The treatment agent according to this embodiment, the method for post-treating a metal material using the treatment agent, and the method for producing a metal material having a chemical conversion coating will be described below in order. Note that the present invention can be modified as desired within the scope of the gist of the invention, and is not limited to the specific embodiment described below.
[0009] <Compound or polymer (A)> The compound or polymer (A) includes at least one selected from a compound or polymer having -NH2, a compound or polymer having -NH2 and -NH-, and a compound or polymer having -NH-. All of them are water-soluble or water-dispersible, and may have a branched chain, a cyclic structure, or both a branched chain and a cyclic structure. The polymer may be a homopolymer or a copolymer. The homopolymer and the copolymer may form a salt. Examples of the salt include hydrochloride, sulfate, acetate, and the like. The term "water-dispersible" refers to having wettability with water.
[0010] The compound or polymer having -NH2 is not particularly limited as long as at least a portion of the substituents of the subunits in the compound or polymer has -NH2, and examples thereof include, but are not limited to, methylamine, ethylamine, isopropylamine, ethylenediamine, 3,3-dimethyl-2-butylamine, sec-butylamine, polyvinylamine, polyallylamine, and the like. The compound or polymer having -NH2 and -NH- is not particularly limited as long as at least a portion of the substituents of the subunits in the compound or polymer have -NH2 and -NH-. Examples of the compound or polymer include, but are not limited to, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, N,N'-bis(2-aminoethyl)-1,3-propanediamine, N,N'-bis(3-aminopropyl)ethylenediamine, polyethyleneimine, hexaethyleneheptamine, heptaethyleneoctamine, and nonaethylenedecamine. The compound or polymer having -NH- is not particularly limited as long as at least a part of the substituents of the subunits in the compound or polymer has -NH-. Examples of the compound or polymer having -NH- include, but are not limited to, dimethylamine, diethylamine, N-ethylmethylamine, N-methylisopropylamine, diisopropylamine, polydiallylamine, cationic acrylic resin, cationic urethane resin, and the like.
[0011] The copolymer is not particularly limited as long as it contains, for example, vinylamine, allylamine, diallylamine, etc., and examples thereof include copolymers of allylamine and diallylamine, copolymers of vinylamine and allylamine, copolymers of vinylamine and diallylamine, etc. Other examples include copolymers containing cationic urethane polymers. The copolymer may be an alternating copolymer, a random copolymer, a block copolymer, or a graft copolymer.
[0012] The compound or polymer (A) may be used alone or in combination in the treatment agent according to the present embodiment. Examples of combinations of two or more include polyallylamine and polyethylene. Examples of the polyallylamine and polydiallylamine include, but are not limited to, polyallylamine and polydiallylamine, polyallylamine and polyvinylamine, polyethyleneimine and polydiallylamine, polyethyleneimine and polyvinylamine, and polydiallylamine and polyvinylamine.
[0013] The weight average molecular weight of the compound or polymer (A) used in the present embodiment is usually 60 to 300,000, and preferably 60 to 100,000.
[0014] When polyallylamine is used as the polymer having the -NH2 group and exhibiting water solubility or dispersibility, the weight average molecular weight thereof may be about 300 to 5,000. When polyethyleneimine is used as the polymer having --NH.sub.2 and --NH.sub.-- and exhibiting water solubility or water dispersibility, its weight average molecular weight can be about 300 to 100,000. When polydiallylamine is used as the polymer having --NH-- and exhibiting water solubility or dispersibility, the weight average molecular weight thereof can be about 300 to 50,000. When a cationic urethane resin is used as the above-mentioned polymer having --NH--, which is water-soluble or water-dispersible, the weight average molecular weight thereof can be about 1,000 to 1,000,000. The weight average molecular weight is a value measured by GPC (gel permeation column chromatography) and converted into polystyrene.
[0015] The amount of the compound or polymer (A) that can be used to prepare the treatment agent according to this embodiment is not particularly limited, but is preferably within the range of 1 to 20,000 mg / L in terms of solid content mass, and more preferably within the range of 5 to 10,000 mg / L in terms of solid content mass, relative to the total amount of the treatment agent.
[0016] <Metal acid ion (B)> The treatment agent of the present embodiment preferably contains at least one metal acid ion (B) selected from molybdate ions and / or tungstate ions. The source of the metal acid ion (B) is not particularly limited as long as it can provide the metal acid ion (B) by mixing with an aqueous medium. For example, sodium molybdate, ammonium molybdate, potassium molybdate, lithium molybdate, calcium molybdate, sodium tungstate, ammonium tungstate, potassium tungstate, lithium tungstate, calcium tungstate, etc. These may be used alone or in combination of two or more. The content of the metal acid ion (B) in the treatment agent is not particularly limited, but is usually within the range of 0.01 to 1000 mmol / L, and preferably within the range of 0.1 to 500 mmol / L, calculated as molybdenum and / or tungsten.
[0017] (organic acid) The treatment agent according to the present embodiment may further contain the following organic acid. When the treatment agent according to the present embodiment further contains an organic acid, the effect of the present invention is further improved. The organic acid is not particularly limited, and may be, for example, an organic acid having one carboxyl group and / or mesyl group and a carbon number of 3 or less. Specific examples of organic acids having one carboxyl group and / or mesyl group and a carbon number of 3 or less include formic acid, acetic acid, lactic acid, propionic acid, trifluoroacetic acid, methanesulfonic acid, and trifluoromethanesulfonic acid. The organic acid may be used alone or in combination with two or more other organic acids in the treatment agent according to this embodiment. Examples of combinations of one or more acids include formic acid and acetic acid, formic acid and lactic acid, formic acid and methanesulfonic acid, acetic acid and lactic acid, acetic acid and methanesulfonic acid, and lactic acid and methanesulfonic acid.
[0018] The amount of the organic acid to be added is not particularly limited, but is preferably in the range of 10 to 10,000 mg / L, and more preferably in the range of 100 to 5,000 mg / L, based on the total amount of the treatment agent.
[0019] The pH of the treatment agent according to the present embodiment is not particularly limited, but is usually 7.0 or more, may be 8.0 or more, may be 9.0 or more, may be 10.0 or more, and is usually 14.0 or less, may be 13.0 or less, may be 12.0 or less. Here, the pH in this specification is a value measured for the treatment agent at 25°C using a pH meter. A pH adjuster may be used to set the pH of the treatment agent within the above range. The pH adjuster that can be used when it is desired to increase the pH is not particularly limited, but for example, an aqueous solution of sodium hydroxide, an aqueous solution of potassium hydroxide, ammonia water, triethanolamine, triethylamine, etc. are preferable. On the other hand, the pH adjuster that can be used when it is desired to decrease the pH is not particularly limited, but for example, formic acid, acetic acid, nitric acid, lactic acid, methanesulfonic acid, etc. are preferable. It should be noted that one or more of these pH adjusters may be used.
[0020] The treatment agent according to the present embodiment is prepared as a liquid. The method for producing the liquid is not particularly limited, but for example, the liquid can be prepared by mixing the compound or polymer (A) with water, and further mixing a source of the metal acid ion (B) or the organic acid as necessary. The liquid medium is not particularly limited, but water (deionized water, distilled water) is preferable. In addition, as the liquid medium, a mixed solvent obtained by mixing a hydrophilic solvent (e.g., a lower alcohol) with water may be used as long as the compound or polymer (A) can be dissolved or dispersed therein.
[0021] In addition, when a metal material having a chemical conversion film is post-treated using the treatment agent according to this embodiment, a part of the metal material having the chemical conversion film may dissolve and a metal component may be mixed into the treatment agent. Therefore, the treatment agent may contain metal components such as Fe, Zn, Al, and Mg. The same applies to components that are inevitably mixed in during operation, such as Zr. These components may be unavoidably mixed into the treatment agent, or may be intentionally included in the treatment agent. Examples of counter ions sourced from the compound for adjusting the metal components and acid components sourced from the acid compound for adjusting pH may include carbonate ions, nitrate ions, silicate ions, and sulfonate ions as anion components of acids and salts.
[0022] (Post-treatment method for metal materials) Another embodiment of the present invention relates to a post-treatment method in which the treating agent described above is contacted with a metal material having a conversion coating.
[0023] The post-treatment method includes a post-treatment step of contacting the treatment agent according to the embodiment of the present invention with the surface or the surface of a metal material having a chemical conversion coating. The post-treatment step may include washing the metal material having a chemical conversion coating with water after the post-treatment step. Also, the method may include washing the metal material having a chemical conversion coating with water before the post-treatment step and after the chemical conversion treatment step. Furthermore, a pretreatment step may be included before the chemical conversion treatment step. A degreasing step, which is called degreasing and removes oil and deposits from the surface of the metal material, may be included before the pretreatment step. The degreasing step is not particularly limited, and a known method can be applied. Water washing may or may not be performed after the degreasing step. In addition, a pickling treatment and / or an oxide film removal treatment, which is called pickling and removes iron oxide, zinc oxide, and the like from the surface of the metal material, may be included before the pretreatment step. The method of the pickling treatment and / or the oxide film removal treatment is not particularly limited, and a known method can be applied.
[0024] The method for contacting the metal material having the chemical conversion coating with the treatment agent includes known contact methods, such as immersion treatment, spray treatment, pouring treatment, or a combination of these. The contact with the treatment agent is preferably carried out at a predetermined temperature for a certain period of time. The contact temperature is preferably 5°C or higher and 60°C or lower, and more preferably 10°C or higher and 50°C or lower, but is not limited to these temperatures. The contact time is preferably 5 to 600 seconds, and more preferably 10 to 300 seconds, but is not limited to these treatment times.
[0025] Another embodiment of the present invention relates to a method for producing a metal material having a chemical conversion coating, the method including a chemical conversion treatment step of forming a chemical conversion coating on the metal material before contacting the above-mentioned treatment agent with the surface of the metal material. The chemical conversion treatment step is not particularly limited as long as it is a treatment for forming a chemical conversion coating, and examples thereof include a zirconium chemical conversion treatment step, a titanium chemical conversion treatment step, a hafnium chemical conversion treatment step, and a vanadium chemical conversion treatment step. The above-mentioned various chemical conversion treatment steps may be performed alone, or two or more steps may be combined and performed sequentially. In addition, when two or more steps are combined, water washing may or may not be performed after each post-process, or some water washing may be omitted. The treatment temperature and contact time in the chemical conversion treatment step can be appropriately set depending on the type of chemical conversion treatment step, the concentration of the chemical conversion treatment agent, etc.
[0026] An embodiment of the present invention also relates to a method for producing a coated metal material, which includes a coating step of coating the surface of a metal material having the above-mentioned chemical conversion coating and having been subjected to a post-chemical conversion treatment. The present invention also relates to a coated metal material having a coating film on the surface of a metal material having a chemical conversion coating obtained by the above-mentioned production method. The coating method is not particularly limited, and known methods such as rolling coating, electrodeposition coating (e.g., cationic electrodeposition coating), spray coating, hot spray coating, airless spray coating, electrostatic coating (e.g., electrostatic powder coating), roller coating, curtain flow coating, brush coating, bar coating, and fluidized bed immersion method can be applied. Note that after the coating step, a drying step (including a baking step and a curing step) for drying the paint on the surface of the coated metal material may be performed. Furthermore, before the painting step, the surface of the metal material having a chemical conversion coating that has been subjected to a post-chemical conversion treatment may or may not be washed with water. Furthermore, before the painting step, the surface of the metal material having a chemical conversion coating that has been washed with water or that has not been washed with water may or may not be dried.
[0027] Examples of the paint include known paints such as oil-based paints, cellulose derivative paints, phenolic resin paints, alkyd resin paints, aminoalkyd resin paints, urea resin paints, unsaturated resin paints, vinyl resin paints, acrylic resin paints, epoxy resin paints, polyurethane resin paints, silicon resin paints, fluororesin paints, rust-preventive paints, antifouling paints, powder paints, cationic electrodeposition paints, anionic electrodeposition paints, water-based paints, and solvent-based paints. The coating process may involve one coating or two or more coatings using the same or different paints. The drying process is a process for drying and curing the applied paint. Examples of drying methods include natural drying, reduced pressure drying, convection-type heat drying (e.g., natural convection-type heat drying, forced convection-type heat drying), radiation-type drying (e.g., near-infrared drying, far-infrared drying), ultraviolet curing drying, electron beam curing drying, vapor curing, and baking drying. These drying methods may be carried out alone or in combination of two or more.
[0028] Known methods can be used for the cationic electrodeposition coating. For example, a cationic electrodeposition coating containing an amine-added epoxy resin and a blocked polyisocyanate curing agent as a curing component is used as the coating material, and a metal material having a chemical conversion coating is immersed in the coating material. The cationic electrodeposition coating is carried out, for example, by applying a voltage in the cathodic direction to the metal material having a chemical conversion coating using a rectifier while maintaining the temperature of the coating material at a predetermined temperature and stirring the coating material. The cationic electrodeposition coating is carried out by the following method. The metal material thus subjected to cationic electrodeposition coating is washed with water and baked to form a coating film on the chemical conversion coating. Baking is carried out for a certain period of time at a specified temperature range. Specifically, baking is carried out at 170°C for 20 minutes. When applying a cationic electrodeposition coating method using a cationic electrodeposition paint, it is preferable to control the sodium ion concentration in the treatment agent used in, for example, the degreasing process, pretreatment process, various chemical conversion treatment processes, post-chemical conversion treatment process, etc. to less than 500 ppm by mass.
[0029] Known methods can be used for coating the powder paint, such as spray coating, electrostatic powder coating, and fluidized bed immersion. Examples of the powder paint include those containing polyester resin and a curing agent such as a blocked isocyanate curing agent, a β-hydroxyalkylamide curing agent (see, for example, JP 2011-88083 A) or triglycidyl isocyanurate. Baking is performed for a certain period of time at a predetermined temperature range. Specifically, baking is performed at 150 to 250°C for 20 minutes.
[0030] As a coating method such as spray coating, electrostatic coating, bar coating, etc., using the above-mentioned solvent paint, a known method can be applied. Examples of the solvent paint include those containing resins such as melamine resin, acrylic resin, urethane resin, polyester resin, etc., and organic solvents such as thinner. Baking is performed for a certain period of time at a predetermined temperature range. Specifically, it is performed at 130°C for 20 minutes.
[0031] The coating film obtained by the coating process may be a single layer or multiple layers. In the case of multiple layers, the paints for forming the various coating films, the coating method using the paints, the drying method of the coated metal material, etc. may be the same or different.
[0032] In this embodiment, the type of metal material that can be used as the target of the post-treatment process is not particularly limited. Examples include steel materials (e.g., cold-rolled steel sheets, hot-rolled steel sheets, high-tensile steel sheets, tool steels, alloy tool steels, spheroidized graphite cast iron, gray cast iron, etc.); plated materials, such as zinc-plated materials (e.g., electrolytic zinc plating, hot-dip galvanizing, etc.), zinc alloy-plated materials (e.g., alloyed hot-dip galvanizing, Zn-Al alloy plating, Zn-Al-Mg alloy plating, electrolytic zinc alloy plating, etc.), aluminum-plated materials, etc.; aluminum materials or aluminum alloy materials (e.g., 1000 series, 2000 series, 3000 series, 4000 series, 5000 series, 6000 series, aluminum castings, aluminum alloy castings, die-cast materials, etc.); magnesium materials or magnesium alloy materials; zinc materials, such as pure zinc materials, zinc alloy materials; tin materials, such as pure tin materials, tin alloy materials; lead materials, such as pure lead materials, lead alloy materials.
[0033] The metal material having a chemical conversion coating can be produced by the above-mentioned method for producing a metal material having a chemical conversion coating. Examples of the chemical conversion coating include a zirconium chemical conversion coating, a titanium chemical conversion coating, a hafnium chemical conversion coating, and a vanadium chemical conversion coating. The chemical conversion coating may be one layer or two or more layers. Here, when a zirconium chemical conversion coating, a titanium chemical conversion coating, a hafnium chemical conversion coating, and / or a vanadium chemical conversion coating is formed, the mass of the formed chemical conversion coating is 5 mg / m2 in terms of the mass of zirconium, titanium, hafnium, or vanadium in the chemical conversion coating per unit area of the metal material surface. 2 More than 500mg / m 2 Preferably, it is 10 mg / m or less. 2 More than 250mg / m 2 It is more preferable that the content of the metal is equal to or less than 100%, but the present invention is not limited to this range. When two or more metals are contained, the total content of the metals is preferably within the above range.
[0034] The amount of zirconium, titanium, hafnium, or vanadium in a chemical conversion coating such as a zirconium chemical conversion coating, a titanium chemical conversion coating, a hafnium chemical conversion coating, or a vanadium chemical conversion coating can be measured by dissolving the chemical conversion coating in concentrated nitric acid and then performing ICP emission spectrometry, or by analyzing a metal material having a chemical conversion coating by X-ray fluorescence analysis.
[0035] The coated metal material can be manufactured by the above-mentioned method for manufacturing a coated metal material. Here, the coating film formed on the coated metal material may be a single layer or multiple layers. In the case of multiple layers, the paint, coating method, drying method, etc. of each layer may be the same or different. The thickness of the coating film may be thick, exceeding 100 μm, or thin, less than 5 μm. For example, in the case of electrodeposition coating, the coating film is generally applied to a thickness of about 10 to 30 μm, but it may be thick, such as 100 μm, or thin, such as 3 μm. EXAMPLES
[0036] The effects of the present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.
[0037] <Preparation of post-chemical treatment agent> Chemical post-treatment agents 1 to 33 were prepared by adding a compound or polymer (A) and a source of metal acid ion (B) to water to give a predetermined molar concentration as shown in Table 1. The chemical post-treatment agents were prepared using the following A1 to A15 and B1 to B4 as the compound or polymer (A) and the source of metal acid ion (B). The pH of the chemical post-treatment agents was 10. A1: Ethylenediamine Tokyo Chemical Industry Co., Ltd. A2: Diethylenetriamine Tokyo Chemical Industry Co., Ltd. A3: Triethylenetetramine Tokyo Chemical Industry Co., Ltd. A4: Tetraethylenepentamine Tokyo Chemical Industry Co., Ltd. A5: Pentaethylenehexamine Tokyo Chemical Industry Co., Ltd. A6: Epomin (registered trademark) SP-200 (Japan Catalyst Co., Ltd.) A7; 1,3-Diaminopentane Tokyo Chemical Industry Co., Ltd. A8: 2-Methyl-1,3-propanediamine Tokyo Chemical Industry Co., Ltd. A9; 3,3'-Diamino-N-methyldipropylamine Tokyo Chemical Industry Co., Ltd. A10: Tris(3-aminopropyl)amine Tokyo Chemical Industry Co., Ltd. A11: 1,3-Diamino-2-propanol Tokyo Chemical Industry Co., Ltd. A12;PAA-01 Nittobo Medical Co., Ltd. A13; PAS-410C Nittobo Medical Co., Ltd. A14: Superflex 620 Daiichi Kogyo Seiyaku Co., Ltd. A15; PAS-21CL Nittobo Medical Co., Ltd. B1: Sodium molybdate dihydrate Junsei Chemical Co., Ltd. B2: Ammonium molybdate (tetrahydrate) Kishida Chemical Co., Ltd. B3: Sodium tungstate dihydrate, Nacalai Tesque, Inc. B4: Ammonium paratungstate, Nippon Inorganic Chemical Industry Co., Ltd.
[0038] [Table 1]
[0039] [Preparation of painted metal materials] <Metal materials> The metal material is cold-rolled mild steel plate (SPC) specified in JIS G3141:2011. C: Thickness 0.8 mm), hot-dip galvanized steel sheet specified in JIS G3302:2012 (SGCC: thickness 0.8mm), alloying melting specified in JIS G3302:2012 Galvanized steel sheet (SCGA: thickness 0.8 mm) and JIS H4000:2014 The specified aluminum alloy plates (A6061: thickness 0.8 mm) were prepared and cut to a size of 70 mm length x 150 mm width. In the evaluation of the painted metal material described below, the surface with burrs on the edge of the metal material was used as the evaluation surface. The height of the burrs was approximately 100 μm.
[0040] <Degreasing treatment for metal materials> Various metal materials were immersed in an alkaline degreasing agent [an aqueous solution of Fine Cleaner E2093 (manufactured by Nihon Parkerizing Co., Ltd.) in which agent A was mixed with agent B at 13 g / L and 11 g / L in water] at 45°C for 2 minutes to remove oil and dirt from the surfaces of the metal materials. The surfaces of the metal materials were then washed with water.
[0041] <Chemical conversion treatment> The various metal materials that had been degreased as described above were immersed in a 50 g / L aqueous solution of a zirconium conversion treatment agent (Palcido 1500, manufactured by Nippon Parkerizing Co., Ltd.) at 40°C for 120 seconds to produce metal materials on which a zirconium conversion coating was formed. In Example 36, a metal material (SCGA) that had been degreased was immersed for 120 seconds at 40°C in an aqueous solution containing 50 g / L of a zirconium conversion treatment agent (Pulseed 1500, manufactured by Nihon Parkerizing Co., Ltd.) to which 100 mg / L of KBM-603 (manufactured by Shin-Etsu Chemical Co., Ltd.) had been added, to produce a metal material on which a zirconium conversion coating was formed. In addition, in Example 37, a metal material (SCGA) that had been degreased was immersed for 120 seconds at 40°C in an aqueous solution containing a 50 g / L aqueous solution of zirconium conversion treatment agent (Pulseed 1500, manufactured by Nihon Parkerizing Co., Ltd.) to which 10 mg / L of copper (II) sulfate pentahydrate (Nacalai Tesque, Inc.) was added, in terms of copper, to produce a metal material on which a zirconium conversion coating was formed.
[0042] <Post-treatment for metal materials> The various metal materials (Examples 1 to 37 and Comparative Example 2) that had been subjected to the above chemical conversion treatment were immersed in various post-chemical conversion treatment agents shown in Table 2 at 25° C. for 90 seconds to carry out post-treatment.
[0043] <Electrodeposition coating treatment for metal materials> The metal material on which the zirconium conversion coating was formed was washed with pure water, and then electrolysis was performed for 180 seconds at a voltage of 200 V using various metal materials as cathodes and a cationic electrodeposition paint (GT-100, manufactured by Kansai Paint Co., Ltd.) to deposit the coating film components on the entire surface of the metal material. Thereafter, the metal material was washed with pure water and baked for 20 minutes at 170°C (PMT: maximum temperature of the metal material during baking) to prepare a coated metal material. The coating film thickness of the coated metal material was adjusted to 20 μm. The coated metal materials prepared at this time were designated as Examples 1 to 37 and Comparative Examples 1 and 2, as shown in Tables 2 and 3. In Comparative Example 1, no post-chemical conversion treatment was performed.
[0044] [Table 2]
[0045] [Table 3]
[0046] <Corrosion resistance evaluation> In order to confirm the corrosion resistance of the edge burrs of each of the coated metal materials prepared in Examples 1 to 37 and Comparative Examples 1 and 2, each coated metal material was placed in a combined cycle tester and subjected to 100 cycles of combined cycle testing in accordance with JASO-M609-91. After 100 cycles, the maximum bulge width from the burrs generated during cutting was measured, and the corrosion resistance of the edge burrs was evaluated according to the following evaluation criteria. In order to evaluate the edge burrs, no tape seal was applied to the edges and backsides of each coated metal material. The results are shown in Tables 4 and 5. Evaluation criteria B and above were considered to be within the practical range. (Evaluation Criteria) S: The maximum bulge width is less than 1.5 mm. (best) A: The maximum bulge width is 1.5 mm or more and less than 2.5 mm. B: The maximum bulge width is 2.5 mm or more and less than 5.0 mm. C: The maximum bulge width is 5.0 mm or more.
[0047] [Table 4]
[0048] [Table 5]
Claims
1. A treatment agent used in post-treatment of a chemical conversion coating formed on or on a surface of a metal material by any one of chemical conversion treatments selected from the group consisting of zirconium chemical conversion treatment, titanium chemical conversion treatment, hafnium chemical conversion treatment, and vanadium chemical conversion treatment, the treatment agent comprising: Water-soluble or water-dispersible, -NH 2 Compounds or polymers having the formula: 2 and one or more compounds or polymers (A) selected from a compound or polymer having —NH—, and a compound or polymer having —NH—, A treatment agent comprising:
2. The treatment according to claim 1 , wherein the pH of the treatment is from 7.0 to 14.
0.
3. 2. The treatment according to claim 1, further comprising at least one metal acid ion (B) selected from a molybdate ion and / or a tungstate ion.
4. A metal material having a coating film, which is obtained by contacting a chemical conversion coating formed by any one of chemical conversion treatments selected from the group consisting of a zirconium chemical conversion treatment, a titanium chemical conversion treatment, a hafnium chemical conversion treatment, and a vanadium chemical conversion treatment with the treatment agent according to any one of claims 1 to 3, and then coating the resulting metal material.
5. A method for producing a coated metal material having a coating film, comprising the steps of: forming a conversion coating on the surface or on the surface of a metal material by a conversion treatment selected from the group consisting of a zirconium conversion treatment, a titanium conversion treatment, a hafnium conversion treatment, and a vanadium conversion treatment; a post-chemical conversion treatment step of contacting the chemical conversion coating with a treatment agent; A coating process for coating the surface of the metal material having the chemical conversion coating film that has been subjected to the chemical conversion post-treatment process. The treatment agent is Water-soluble or water-dispersible, -NH 2 Compounds or polymers having the formula: 2 and a compound or polymer having -NH-, and a compound or polymer having -NH-.
6. The method for producing a coated metal material according to claim 5, wherein the pH of the treatment agent is from 7.0 to 14.
0.
7. The method for producing a coated metal material according to claim 5 or 6, wherein the coating step includes a step of performing cathodic electrodeposition coating.
Citation Information
Patent Citations
Improved method for anticorrosion pretreatment of metal surfaces including steel, galvanized steel, aluminum, magnesium, and / or zinc-magnesium alloys
JP2019518874A
Pretreatment agent, pretreatment method, metal material having chemical conversion film and manufacturing method therefor, and painted metal material and manufacturing method therefor
WO2019087320A1
